THE INFLUENCE OF JIGSAW LEARNING MODEL ON THE ABILITY TO WRITE A DESCRIPTION OF STUDENTS OF GRADE X SMAN 1 BANYUMAS PRINGSEWU - Anggraeni, Leni (JLCEdu (Journal of Learning and Character Education), 2021)
In writing language activities that students often do is composing, because composing teaches the ability to make good and correct sentences according to knowledge and can assemble them into paragraphs. Writing skills are language skills that need to be possessed by students because with writing skills students can communicate ideas or ideas in writing one of them through the activity of writing a descriptive essay. The description is a technique of writing using detail to make the reader seem to be on the scene, feel, experience, see and hear about an event or scene. The results of the research studies that have been conducted show that there is an influence on the use of the Jigsaw method on the ability to write descriptions in grade X students of Semester II SMA Negeri 1 Banyumas Pringsewu Regency.